Pengaruh Pupuk Batu bara dan Kalium Terhadap Bunga dan Produksi Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) - Hasim, Ridwan Hasim; Syafrinal; Khoiri, M Amrul (Universitas Medan Area, 2025)
This study discusses the Effect of Coal and Potassium Fertilizers on the Flower and Production of Oil Palm Plants (Elaeis guineensis Jacq.). This study aimed to determine the interaction between coal fertilizer and potassium fertilizer, as well as the influence of each single factor, on the flower and production of oil palm plants, as well as the correlation between the observed variables. This study was conducted experimentally using a factorial Complete Random Design (RAL) with two aspects of treatment. The first aspect is the dosage of coal fertilizer with three levels: 0, 1, and 2 kg per plant per 6 months. The second aspect is the dosage of potassium fertilizer with 3 levels: 3, 4, and 5 kg per plant per 6 months. The results of the analysis showed that the combination of 1 kg of coal fertilizer and 5 kg of potassium fertilizer per plant was the best treatment. This treatment has been proven to accelerate the ripening time of fruit and significantly increase the production of oil palm plants.